ALUMINIUM COOKING UTENSILS: LEVEL OF USER'S PERCEPTION REGARDING HEATH HAZARDS. (Fiep Bulletin - online, 2014)
During the cooking process some compounds, from the cooking utensil, may be released in the food. Thus, the utilization of pots containing heavy metals, such as aluminum, can represent a risk for human health, since this metal can affect several neurophysiological processes, including the ones responsible for Alzheimer disease. Objective: Assess research subject's knowledge about the risks related to regular use of aluminum cooking utensils and a possible relation between this use and Alzheimer disease. Methods: This study was carried out using a descriptive, cross-sectional survey conducted with 100 subjects. The subjects were asked to fill in a form composed by objective questions, which were used as variants of the test. The data were expressed in tables and simple frequency charts. The ethical aspects were in agreement with the resolution Nº 196/96 (CNS-MS). Results: The results showed that 35% of the subjects regularly use a wooden spoon to stir the food in aluminum pots; 44% store the food in aluminum pots for about 12 h and 51% are not aware of the risks presented by the use of aluminum cooking utensils. The majority of the subjects have average income and basic educational level, what might lead to shallow knowledge concerning the risks related with heavy metals. Besides, nowadays the economic factors seem to have a great influence in people's purchase choices for cooking utensils. None of the interviewed subjects suffered from Alzheimer disease. However, a minority of them (10%) had a history of relatives presenting the disease. A small group of subjects (2%) presented two main symptoms related with Alzheimer disease: memory loss and loss of cognitive abilities. These results suggest that the use of aluminum cooking utensils may not be related with Alzheimer disease development, since the great majority of subjects assessed did not present symptoms of this disease.
Keywords: Aluminum; cooking utensils; Alzheimer